THE IMPORTANCE OF VITAGEN EDUCATION IN THE EDUCATIONAL PROCESS (Web of Teachers: Inderscience Research, 2025)
This article discusses the active interest of the student in the introduction of innovations into the educational process, the conceptual rules of life education technology, the transformation of life experiences into educational values, reliance on the individual’s consciousness, his ideas about the versatility of the educational process, and life information consisting of several stages of life experience.